Movimiento de Mujeres Indígenas por el Buen Vivir: marchando entre la política, lo político y lo ontológicamente diverso en Argentina - Carolina Álvarez Ávila (Centre de Recherches sur les Mondes Américains, 2019)
In this work I am interested in reflecting on the group called the Movement of Indigenous Women for Good Living in Argentina that, since 2015, has been generating different actions in the public arena, denouncing various conflicts that affect indigenous peoples in the country and proposing a new cohabitability pact that ensures a Good Living. We chose to focus on the political dimension of their claims and proposals, trying to make the analysis contribute to reflecting on indigenous politics on their own terms. We analyze the formation of the group and its self-registration as indigenous women, attending to possible connections and disconnections with other feminisms, in order to track the logic of policy and politics. We also investigate their slogans, claims and proposals, focusing finally on their proposal of Good Living. This analysis allows us to glimpse how they move between these two logics of action but also urge us to schedule discussions that anthropologically concern the relationship between ontology and politics.